Pacing strategy and role of expertise in broken 800's workouts regarding the 800-m run - Blasco-Lafarga, C.; Montoya-Vieco, A.; Mateo-March, M.; Martinez-Navarro, I.; Gonzáles, P.; Botella, A.; Roldán, A. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Introduction It`s been described the existence of different pacing strategies in 800-m races. When racing the clock (i.e. improving Season Best [SB]), athletes describe a Positive Pacing (PP) where speed gradually declines throughout the race. When tactical running (i.e. qualifying races) there is a more Variable Pacing [VP], or even a parabolic pacing (1). On the other hand, coaches use speed endurance workouts (i.e. Broken 800`s [B8]) to develop the athletes` ability to tolerate fatigue while running at the race pace (2-5). However, little is known about this workout`s influence on pacing. Therefore, our purpose was to analyze athletes` pacing in B8 regarding to that in the 800-m run; and to investigate whether this pacing is an age-related ability. Methods 19 male 800-m runners, belonging to either Under23 & Senior (GA; n=10; SB= 113.75±4.08 s) or Juvenile & Junior category (GB; n=9; SB= 120.92±3.33 s), performed a B8 consisting in 2x(4x200-m) at 102% (SB), recovering 30 s between repetitions and 15 min between sets. Time for 200-m segments (T200) was obtained by recording with a CASIO HS EX-FH100 camera (420Hz) placed in the centre of the track, and later video analysis (Kinovea-0.8.7). A two-way Repeated Measures ANOVA was conducted, with 1 intra-subject factor: Pacing (T200 differences), and 1 grouping factor: age category (GA vs. GB). Further Bonferroni adjustments were conducted. The study, approved by University of Valencia Ethics Committee, followed the standards, controlling for athletes` previous tapering, rest, nutrition and hydration. Results Univariate contrast showed significant T200 differences both on Pacing (p<0.001) and on the interaction Age-category*Pacing (p<0.05). Figure 1 reflexes Bonferroni adjustments (see numbers and letters for T200 significant differences on Pacing; Stars for T200 performance differences between categories). Regarding performance, GA ran always significantly quicker except for B81. Regarding pacing*category, GA maintained a slight and progressive velocity impairment, thus PP, although neither linearly nor significantly for intermediate consecutive T200. In fact, after 15 minutes of recovery, GA ran B8a even quicker than B81, although with no significance. GB ran a VP first set, followed by a second PP set. Conclusions B8 workout is more related to the PP in 800-m racing the clock events than to tactical pacing variations. However, lack of within signification in intermediate T200, and category significant differences, suggest a certain possibility to pacing variation and choice learning. Pacing confirms to be an age-related factor.